Reseña de Pilkington, A. (2000). Poetic effocts. - Guijarro Morales, José Luis (Pragmalingüística, 2010)
<!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Se trata de una reseña sobre Pilkington, A. (2000). Poetic effocts.